2019
DOI: 10.1088/1742-6596/1244/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Industry System Integration of Drug Distribution on Pharmaceutical Installation Based on Supply Chain Management

Abstract: Supply Chain Management (SCM) requires all sectors to collaborate, coordinate, communicate and exchange information to improve inter-sector productivity. It takes information technology and supplies chain concepts to integrate all sector activities involved such as, in the health field such as clinics and health services. System integration will create good communication and exchange of information, and data availability will be fulfilled. This research will try to offer information technology in the form of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Pharmaceutical warehouses in many countries such as Turkey are one of the health stakeholders that provide the purchase, sale and distribution of pharmaceutical products within the scope of current legal circumstances ( Arslan, 2020 , Tengilimoğlu et al, 0000 ). When the studies on pharmaceutical warehouses are examined in the literature, it has been observed that there are generally studies aimed at establishing an effective supply chain ( Abideen and Mohamad, 2021 , Abideen and Mohamad, 2020 , Abideen and Binti Mohamad, 2019 , Jiang et al, 2019 , Özkan, 2017 , Qashlim and Basri, 2019 , Tat et al, 2020 ). However, the threat posed by the COVID-19 pandemic to the whole world has caused an emergency in the world ( Barshooi and Amirkhani, 2022 ) and it has become necessary to put forward studies with a new perspective in order to ensure full and timely access to the drugs of those infected with the Coronavirus Disease 2019 (COVID-19) virus and to provide a full-time supply of drugs of COVID-19.…”
Section: Introduction and Related Studiesmentioning
confidence: 99%
“…Pharmaceutical warehouses in many countries such as Turkey are one of the health stakeholders that provide the purchase, sale and distribution of pharmaceutical products within the scope of current legal circumstances ( Arslan, 2020 , Tengilimoğlu et al, 0000 ). When the studies on pharmaceutical warehouses are examined in the literature, it has been observed that there are generally studies aimed at establishing an effective supply chain ( Abideen and Mohamad, 2021 , Abideen and Mohamad, 2020 , Abideen and Binti Mohamad, 2019 , Jiang et al, 2019 , Özkan, 2017 , Qashlim and Basri, 2019 , Tat et al, 2020 ). However, the threat posed by the COVID-19 pandemic to the whole world has caused an emergency in the world ( Barshooi and Amirkhani, 2022 ) and it has become necessary to put forward studies with a new perspective in order to ensure full and timely access to the drugs of those infected with the Coronavirus Disease 2019 (COVID-19) virus and to provide a full-time supply of drugs of COVID-19.…”
Section: Introduction and Related Studiesmentioning
confidence: 99%
“…The competence of information system can be measured by its ability to provide information to help business processes and make the right decisions [11]. Integration of information system can produce more accurate data for top level management to make decision for market.Integrated system when implemented will enable best performance in all sector, improved performance influence on financial and operational cost reduction [15].…”
Section: Introductionmentioning
confidence: 99%
“…Qashlim, dkk (2019), hasil penelitiannya menyimpulkan bahwa integrasi sistem informasi dapat menghasilkan data yang lebih akurat bagi manajemen tingkat atas untuk mengambil keputusan pasar. Sistem yang terintegrasi ketika diimplementasikan akan memungkinkan kinerja terbaik di semua sektor, meningkatkan pengaruh kinerja pada pengurangan biaya keuangan dan operasional [2].…”
unclassified